Implementasi Pendidikan Berbasis Boarding School di MAN 2 Sukabumi - E. Komarudin; Siti Qomariyah; Emat Muslihat; Hoerul Kusban (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2025)
This study aims to explore the implementation of education at MAN 2 Sukabumi, which is based on a boarding school system. The background of this research highlights the increasing need for integrated educational approaches that combine academic learning and character building in a structured environment. The objective of this research is to analyze how the boarding school model is applied in MAN 2 Sukabumi and its impact on students' academic and personal development. The research uses a qualitative approach with case study methodology, involving data collection through interviews, observations, and document analysis. The results show that the implementation of the boarding school system at MAN 2 Sukabumi has a positive effect on students' discipline, time management, and academic performance. The vision and mission of the school focus on producing knowledgeable, skilled, and ethical individuals who contribute to society. This study concludes that the boarding school model effectively supports holistic student development.